EKSPRESI VERBAL PENYINTAS SAAT BENCANA: ANALISIS PRAGMATIK ARSIP TSUNAMI ACEH - Faisal; Junaidi; Nurliza, Eli; Ismawirna; Azmi, Nurul; Asriani; Fauziah, Siti Naila (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Expression speech acts are a form of a person's natural expression of what is actually felt. The speech acts of expression of Aceh tsunami survivors provide important information about how the survivors perceived the 2004 tsunami event. Expressing what they thought, believed and felt when they experienced the tsunami. Was the tsunami the apocalypse or a warning from God? One form of speech act of expression is self-centered speech act of expression, which is the speech act of expression of survivors to themselves. How are the forms and functions of self-centered expressive speech acts produced by Aceh tsunami survivors. A qualitative research method with a pragmatic approach is used to examine the data sources, namely 105 manuscripts of the experience stories of the survivors of the 2004 Aceh tsunami collected in a book entitled Tsunami and Their Stories by the Provincial Archives of Nanggroe Aceh Darussalam. The data in this study are excerpts of speech acts of expression of the Aceh tsunami survivors. The data were collected through documentation study, namely reading carefully, identifying, marking, and sorting the data into specific topics. Data analysis was conducted using a qualitative data analysis model, namely reducing data, presenting data, and drawing conclusions. The results showed that the survivors of the 2004 Aceh tsunami expressed 11 forms of self-centered expressive speech acts. The survivors expressed their emotions in accordance with social, cultural, and religious norms. In the context of a religious Acehnese society, the various speech acts of the survivors' expressions reflected a strong faith and acceptance of the disaster as part of God's will. Islam and Acehnese culture build the construction of speech acts of expression centered on the survivors of the 2004 Aceh tsunami. Keywords: self-centered speech acts of expression, Aceh tsunami survivors, Islamic values and Acehnese culture